Posted by
**Anonymous** on
.

IF

f(x) = {(3,5), (2,4), (1,7)}

h(x)= {(3,2), (4,3), (1,6)}

determine each of the following:

(f+h)(1)=

how do I add f and h?

(f o h)(3)=

how would I multiply f and h?

f^-1(x)=

how would I find the inverse of f?

1/f(x)=

how would I do that?

f(1) = 7 and h(1) = 6

(f + h)(x) is by definition f(x) + h(x)

(f o h)(x) is by definition f(h(x))

h(3) = 2

and f(h(3)) = f(2) = 4

So (foh)(3) = 4

f^(-1)(f(x)) = x by definition.

f(x) = {(3,5), (2,4), (1,7)}

If you take, e.g., x = 3, then you see that

f^(-1)(5) = 3. So, you see that you just need to interchanbge the numbers:

f^(-1)(x) = {(5,3), (4,2), (7,1)}